COMPARATIVE PHARMACOKINETICS AND EFFECT ON THE HEMODYNAMICS OF ORIGINAL AND GENERIC NEBIVOLOL IN HEALTHY VOLUNTEERS - E. I. Bambysheva; K. V. Isaeva; M. M. Makhinova; D. T. Guranda; V. G. Belolipetskaya (Столичная издательская компания, 2016)
Beta-blockers are an important part of modern pharmacotherapy in cardiology. The introduction of generics into clinical practice requires clear evidence of bioequivalence to the original drug.Aim. To study the pharmacokinetics and effect on hemodynamic parameters of the original and a generic nebivolol in healthy volunteers in the fasting state. Material and methods. 18 healthy volunteers were included into the randomized open study on cross-balanced design. They received single dose (5 mg) of two compared preparations of nebivolol under fasting condition. The concentration of unchanged nebivolol in blood plasma was determined by gas chromatography-tandem mass spectrometry. Calculation of pharmacokinetic parameters and assessment of the hemodynamic were performed.Results. The concentrations of nebivolol after the original and generic drugs intake did not differ significantly in any time point (AUC0-∞ 41.09±46.82 vs 47.16±66.58 ng•hr/mL and T1/2 30.84±10.78 vs 29.59±12.08 hours, respectively). Blood pressure reduction was slightly more pronounced when taking generic nebivolol, while the reduction in heart rate at 2 and 4 hours - after original nebivolol intake.Conclusion. A comparative pharmacokinetic study of the genetic nebivolol showed its bioequivalence to the original drug. The effect on hemodynamic parameters with single dose (5 mg) of generic and original nebivolol in healthy volunteers was comparable.